2021
DOI: 10.1177/14614448211020690
|View full text |Cite
|
Sign up to set email alerts
|

Memes, scenes and #ELXN2019s: How partisans make memes during elections

Abstract: Our article analyses partisan, user-generated Facebook pages and groups to understand the articulation of political identity and party identification. Adapting the concept of scenes usually found in music studies, these Facebook pages and groups act as partisan scenes that maintain identities and sentiments through participatory practices, principally by making and sharing memes. Using a mixed methods approach that combines social media data and interviews during the 2019 Canadian federal election, we find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Recent studies on political movements followed en suite. Meme pages and celebrities, for instance, have been recently characterized to spark instances of political participation in Morocco [34], maintain partisan identity in Canada [35], promote public health behavior [36], or facilitate misinformation [37]. Recent work has focused on the growing role of visuals in protests directly, such as the case of the Hong Kong Protests in 2019 [38].…”
Section: Instagram and The Second Wave Of Black Lives Mattermentioning
confidence: 99%
“…Recent studies on political movements followed en suite. Meme pages and celebrities, for instance, have been recently characterized to spark instances of political participation in Morocco [34], maintain partisan identity in Canada [35], promote public health behavior [36], or facilitate misinformation [37]. Recent work has focused on the growing role of visuals in protests directly, such as the case of the Hong Kong Protests in 2019 [38].…”
Section: Instagram and The Second Wave Of Black Lives Mattermentioning
confidence: 99%
“…Intriguingly, however, we found that circulating memes did not relate to political interest or strength of partisanship—a finding that departs from other scholarship (Johann, 2022)—suggesting that posting political memes is a method of political expression utilized by a wide variety of individuals, including political moderates and the politically uninterested. 3 This is especially interesting given that much of the literature on political memes focuses on their use in partisan groups (e.g., Al-Rawi, 2021; McKelvey et al, 2021) and argues that meme authors are particularly polarized users (Paz et al, 2021). Although political memes can be used to establish like-minded communities online (McKelvey et al, 2021), our results suggest that memes are also created and shared by nonpartisan users as an everyday form of political expression.…”
Section: Discussionmentioning
confidence: 99%
“…3 This is especially interesting given that much of the literature on political memes focuses on their use in partisan groups (e.g., Al-Rawi, 2021; McKelvey et al, 2021) and argues that meme authors are particularly polarized users (Paz et al, 2021). Although political memes can be used to establish like-minded communities online (McKelvey et al, 2021), our results suggest that memes are also created and shared by nonpartisan users as an everyday form of political expression. Meme circulators were, likewise, not more likely to report high levels of participation in political activities or political knowledge; in fact, creators of memes were slightly less likely than other users to score high on political knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations